A new formulation of relativistic dynamics - Warzanskyj Poliscuk, Wsewolod (1989)
A brief revision of Einstein's General Relativity is carried out and some of its inconsistencies are brought to light. The concept of the relativistic force and its components is also considered. Then, the equations of the general motion in the relativistic euclidean 4-space (E-4D) is derived and applied to several types of motion.